Strengths and weaknesses of accessibility instruments in planning practice: technological rules based on experiential workshops - te Brömmelstroet, M.; Curtis, Carey; Larsson, A.; Milakis, D. (Taylor and Francis, 2016)
Accessibility instruments can play a valuable role in urban planning practice by providing a practical framework for exploring and testing relationships between land use and transport infrastructure. Despite many available accessibility instruments, they are still not widely used in planning practice. This paper explores the background of this problem by examining the findings of a EU-funded study on the usability and usefulness of existing accessibility instruments. The study applied 16 instruments in local planning contexts according to a standardized process protocol. The outcomes of these so-called experiential workshops were analysed through a standardized measurement protocol, which included participant observation along with pre- and post-workshop practitioner questionnaires. This broad investigation presents a rich analytical tool for understanding how different types of accessibility measures, spatial resolutions of output and levels of comprehensiveness affect usability and usefulness. Based on this we propose 10 technological rules that (a) can be used directly in practice to improve usability of accessibility instruments and (b) can provide hypotheses to be examined in further academic studies. Our results suggest that instead of striving for the ultimate accessibility measure, it would be more effective to identify which measures could successfully serve different user needs in accessibility planning.